2015
DOI: 10.3762/bjoc.11.169
|View full text |Cite
|
Sign up to set email alerts
|

Latent ruthenium–indenylidene catalysts bearing a N-heterocyclic carbene and a bidentate picolinate ligand

Abstract: SummaryA silver-free methodology was developed for the synthesis of unprecedented N-heterocyclic carbene ruthenium indenylidene complexes bearing a bidentate picolinate ligand. The highly stable (SIPr)(picolinate)RuCl(indenylidene) complex 4a (SIPr = 1,3-bis(2-6-diisopropylphenyl)imidazolidin-2-ylidene) demonstrated excellent latent behaviour in ring closing metathesis (RCM) reaction and could be activated in the presence of a Brønsted acid. The versatility of the catalyst 4a was subsequently demonstrated in R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Since then, a number of additional light-activated systems have been developed, including catalysts with inherent photoswitchable characteristics that do not require the addition of a complementary photoactive compound. Quite recently, Theunissen et al demonstrated exquisite temporal and spatial control over a suite of metathetic transformations using bis­( N -heterocyclic carbene) (bis-NHC) complexes in combination with an oxidizing photocatalyst that induces dissociation of a NHC ligand . A variety of acid-activated catalysts, similar to the acetylacetonate-protected alkylidenes mentioned above, have also been established, such as amidobenzylidene , and aryloxy­benzylidene chelates, among a variety of other Ru chelates. , Similarly, thermally activated catalysts are becoming increasingly widespread. Such catalysts exhibit negligible initiation of a given substrate at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a number of additional light-activated systems have been developed, including catalysts with inherent photoswitchable characteristics that do not require the addition of a complementary photoactive compound. Quite recently, Theunissen et al demonstrated exquisite temporal and spatial control over a suite of metathetic transformations using bis­( N -heterocyclic carbene) (bis-NHC) complexes in combination with an oxidizing photocatalyst that induces dissociation of a NHC ligand . A variety of acid-activated catalysts, similar to the acetylacetonate-protected alkylidenes mentioned above, have also been established, such as amidobenzylidene , and aryloxy­benzylidene chelates, among a variety of other Ru chelates. , Similarly, thermally activated catalysts are becoming increasingly widespread. Such catalysts exhibit negligible initiation of a given substrate at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis involved the reaction of N-heterocyclic carbene bearing precursor complexes M31 , HovII or M32 with excess of 5,7-dichloro-8-hydroxyquinoline or 5,7-dibromo-8-hydroxyquinoline in the presence of excess Cs 2 CO 3 as the base (see Scheme 1 ). The silver-free method [ 41 ] resulted in any case in the formation of at least two new products (as evidenced by thin-layer chromatography) which were separated by means of column chromatography. All obtained complexes are very stable in the solid state and can be stored for several days in solution in the presence of oxygen without any sign of decomposition.…”
Section: Resultsmentioning
confidence: 99%
“…In type II systems, a donor ligand is tethered to one of the anionic ligands. In this case the chelation decelerates both initiation and propagation, and therefore, this layout is optimally used in acid-switchable systems . In the case of type III systems, a chelating carbene ligand is used.…”
Section: Strategies In the Design Of Latent Catalystsmentioning
confidence: 99%